N-Closure and N-Interior in Neutrosophic Topological Spaces - K. Damodharan; M. Vigneshwaran (Neutrosophic Sets and Systems, 2024)
Topology greatly benefits from the concept of δ-cloure. Its quiet nature to extended its proper-ties in other topological spaces. So, with the concept of quasi-coincidence Ganguly and Saha pioneered and extensively examined the notion of δ-closure within the domain of fuzzy topological spaces (FTS). The theory of δ-closure in intuitionistic fuzzy topological spaces (IFTS) was further extended by Seok Jong Lee and Yeon Seok Eom. In this work, the notion of Nδ-closure in Neutrosophic Topological Spaces (NTS) is put forward and discussed.